NOT TUMORAL DISEASES OF VULVA - I. O. Makarov; E. A. Chulkova; N. A. Sheshukova; I. I. Makarova (Акушерство, гинекология и репродукция, 2016)
This paper describes the classification, etiology, diagnosis and treatment of non-neoplastic diseases of the vulva. Terms and kraurosis leukoplakia of the vulva have no clear morphological equivalents, and display only certain clinical manifestations. Sclerosing shingles and squamous hyperplasia, often combined with each other and, in essence, is a single pathological process - with or without lichenification.